Who governs? : democracy and power in an American city - Dahl, Robert A., 1915-2014 (Yale studies in political science ;, 1989)
This book is an attempt to throw new light on an ancient question by examining a single American city in New England. Professor Dahl provides a pluralist theory of local power structure. This will become a classic reference for those seeking an understanding of political behavior in modern urban environments under democratic regimes.